MELINTASI HAMBATAN ETIKA: Tinjauan Terhadap Kemandirian dalam Seleksi Penyelenggara Pemilu Pada KPU dan BAWASLU - Muhammad Irawan Adi Hartono; Robi Cahyadi K; Feni Rosalia; Hertanto (Halu Oleo University, 2023)
Elections can only be held in a credible and fair manner if they are placed by an impartial institution. According to the Constitution, elections are conducted by an independent EMB, with no additional definition of independence. The purpose of this study is to determine the post-reform electoral management institution model and the concept of independence in Article 22E paragraph (5) of the 1945 Constitution as recognized by the Constitutional Court, the research methodology is the normative legal method and the legal and case approach. According to the findings of this study, the post-reform election model is an independent model that does not involve representatives from political parties or employees.